Crystal disassembly and reassembly of heterometallic NiII–TaV oxalate compounds12. Issue 9 (7th March 2015) - Dubraja, Lidija Androš; Matković-Čalogović, Dubravka; Planinić, Pavica
<x xml:space="preserve">Abstract</x> A crystal disassembly/reassembly process was observed in Ni–Ta oxalate systems: solution mediated transformation 1 → 2 is accompanied by spontaneous resolution of cations, whereas transformation 3 → 4 is enabled by replacement of anions.